Use of Magnetic Resonance Neurography for Sensory Nerve Injuries of the Head and Neck - Merel H.J. Hazewinkel, MD; Yenpo Lin, MD; Tim Y. Li, BA; Babacar Cisse, MD, PhD; Ek T. Tan, PhD; Darryl B. Sneag, MD; Lisa Gfrerer, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. Identification of peripheral nerve injuries of the head and neck can be challenging due to a broad spectrum of symptoms from neuropathic pain to headaches and migraine. This article aimed to present the clinical features and diagnostic workup of patients with acute and chronic peripheral nerve injuries of the head and neck using magnetic resonance neurography (MRN), to demonstrate potential advantages compared with conventional magnetic resonance imaging (MRI). Methods:. Patients who presented with suspected peripheral nerve injury were either referred for a conventional MRI or MRN. Patients who underwent nerve exploration for suspected nerve transection and/or neuroma formation on imaging were included in this study. Imaging findings were correlated with intraoperative observations. Results:. Four patients (3 women, 1 man, age range: 34–70 years) were included. Three subjects had a history of head and neck surgery and 1 experienced direct trauma to the medial eyebrow. Clinical symptoms included numbness, allodynia, positive Tinel sign, and pain relief following nerve blocks. Two patients underwent conventional MRI and 2 underwent MRN. MRI provided a vague indication of potential neuromas and failed to accurately depict their locations. MRN offered a comprehensive visualization of the entire nerve path, identifying nerve transection and neuromas, as well as precise location, dimensions, and relation to adjacent bones and muscles. Conclusions:. High-resolution 3-dimensional MRN provides clear visualization of acute and chronic peripheral nerve injuries of the head and neck region, facilitating early diagnosis of nerve injuries in this region and improving diagnostic accuracy, as well as surgical planning and execution.